Model for Implementing Evidence Based Health Care System in Iran - Saeed Manavi; Alireza Olyaee Manesh; Shahram Yazdani; Lida Shams; Taha Nasiri; Armin Shirvani; Hasan Emami Razavi (Tehran University of Medical Sciences, 2013)
Background: Regarding the role and importance of paradigm of evidence based practice and its remarkable impact on the effectiveness and efficiency of clinical services and healthcare, development of an integrated system seems necessary in order to manage dispersed data and ensure using evidence in clinical decision making, thus the aim of this study was designing a model for implementing national system of evidence based health care in Iran.Methodos: This paper is a study of comparative type which has been written in three stages: investigation of structure and process of evidence based practice in selected countries, investigation and analysis of current status in Iran in this regard and recommendation of strategies which make model implementation feasible in the country. Such methods as review of literature, focus group discussion and Delphi technique were used for investigation.Results: According to studies, insuring an evidence based practice culture in the country requires a system called National Evidence Based Health Care System which consists of three subsystems including national system of clinical knowledge management, national evidence-based practice system and integrated national network of clinical effectiveness.Conclusion: The ultimate goal of health care system in every country is maintaining and improving community health. Achievement of this goal depends on effectiveness of delivered services and consistency of the services with national and local priorities. In order to achieve clinical effectiveness, the best practice should be realized in the country, implementation of which requires a set of macro and micro strategies enabling facilitation, promotion or guaranteeing clinical knowledge application in the country.